2016
DOI: 10.1016/j.neuroscience.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine modulates timing of self-initiated saccades

Abstract: The authors thank S. Ohmae, T. Suzuki, and other lab members for valuable comments and AbstractThe ability to adjust movement timing is essential in daily life. Explorations of the underlying neural mechanisms have reported a gradual increase or decrease in neuronal activity prior to self-timed movements within the cortico-basal ganglia loop. Previous studies in both humans and animals have shown that endogenous dopamine (DA) plays a modulatory role in self-timing.However, the specific site of dopaminergic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…According to the above consideration, the pharmacological blockade should improve the performance of canceling contralateral saccadic eye movements. Consistent with our findings, a previous study in monkeys also reported that D1 and D2 antagonist injections into the caudate nucleus affected ipsilateral saccadic eye movements, but not contralateral ones, in a saccade task named the self-timed memory-guided saccade task (Kunimatsu and Tanaka, 2016). In this task, the monkey was required to wait for a predetermined time interval (e.g., 1,100 ± 300 ms after cue offset) before making a saccadic eye movement to a remembered cue location.…”
Section: Discussionsupporting
confidence: 92%
“…According to the above consideration, the pharmacological blockade should improve the performance of canceling contralateral saccadic eye movements. Consistent with our findings, a previous study in monkeys also reported that D1 and D2 antagonist injections into the caudate nucleus affected ipsilateral saccadic eye movements, but not contralateral ones, in a saccade task named the self-timed memory-guided saccade task (Kunimatsu and Tanaka, 2016). In this task, the monkey was required to wait for a predetermined time interval (e.g., 1,100 ± 300 ms after cue offset) before making a saccadic eye movement to a remembered cue location.…”
Section: Discussionsupporting
confidence: 92%
“…Subjects with Parkinson’s disease, for example, show deficits in the estimation and production of interval timing within the range of seconds ( Pastor et al, 1992 ) and exhibit a significant decrease in the magnitude of CNV ( Ikeda et al, 1997 ). In experimental animals, local application of dopamine receptor antagonists into the striatum alters self-timing in monkeys ( Kunimatsu and Tanaka, 2016 ), and more specifically, optogenetic inhibition of nigro-striatal pathways disrupts temporal discrimination in rodents ( Soares et al, 2016 ). However, the firing of midbrain dopamine neurons is known to be generally phasic ( Bromberg-Martin et al, 2010 ) and therefore appears unlikely to continuously keep track of elapsed time during motor preparation, while the gain of transient sensory response might carry temporal information ( Soares et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the roles of the basal ganglia and the cerebellum in self-timing, we compared activity of single neurons in the anterior part of the striatum (caudate nucleus) with those in the posterior part of the cerebellar dentate nucleus in monkeys performing the self-timed saccade task ( Ashmore and Sommer, 2013 ; Kunimatsu and Tanaka, 2012 , 2016 ; Tanaka, 2006 , 2007 ). Because the previous studies have demonstrated that these subcortical regions have common anatomical connections with the medial and lateral frontal cortices involved in temporal processing ( Dum and Strick, 2003 ; Strick et al, 2009 ; McFarland and Haber, 2001 ), we reasoned that these areas might have functional interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the RSG task, evaluation of behavioral performance is likely to engage higher cortical areas 107 , and the processing of feedback on timing performance is likely to engage the basal ganglia 108 . Furthermore, numerous studies have found neural correlates of interval timing across the cortico-basal ganglia circuits 93,[109][110][111][112][113] . Indeed, even within the context of the RSG task, cortico-basal ganglia circuits are likely to be involved in the conversion of a Bayesian estimate computed at the time of Set to an ensuing motor plan for the reproduction of that interval 114 .…”
Section: Discussionmentioning
confidence: 99%